HUMAN RESOURCE DEVELOPMENT AND PUBLIC SERVICE DELIVERY IN NIGERIA; A STUDY OF ANAMBRA STATE CIVIL SERVICE (2007 -2011) - Dr. R. U. Onyekwelu ,Dike, Ego. E (International Journal of Research Science and Management, 2016)
This study is on human resource development and service delivery in Anambra State civil service within the period of 2007-2011. The study seeks to determine the impact of human resources development on services delivery. The Anambra State civil service remains the greatest asset of the state in its quest for socio economic and political transformation. However there is no gain saying the fact that over the years, infrastructural development and service delivery have slackened. Inferred opinions have traced this to an inefficient civil service. The missing factor in many cases is lack of adequate skills and knowledge which are acquired through training and development. Three hypotheses were formulated to guide the study and the multi-stage and simple random sampling techniques were used to select the study sample. The data collected were presented in frequency tables and analysed using percentages and mean scores and the hypotheses were tested using one sample t-test. The findings from the study showed that human resource development programmes helped to a large extent to increase productivity and organization efficiency in the Anambra State civil service. It was also revealed that the existing methods/programes of human resource development in the state civil service are appropriate for the actualization of effective service delivery and that human resource development programmes are significantly related to employee motivation/productivity. The researcher concludes that human resource development programmes in the state civil service have led to positive changes in productivity, service delivery, work attitude and morale of workers. The researcher recommends that the state government should set up regular training and human development programmes that are capable of raising the skills, morale and productivity of civil servants. Also consultants from outside the civil service should be engaged on routine basis to assist in the planning of the content of human resource development programme